Field notes contributed by Paul Martsching, fall 1988 - Martsching, Paulet al (1988)
List of birds and locations contributed by Paul Martsching. The field notes include a detailed description of a Peregrine Falcon. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed/flatbed